ECONOMICS OF BIO-BASED FERTILIZER IN IMPROVING CROP PRODUCTIVITY THROUGH EXTENSION SERVICES DELIVERY - MANOGNYA (African Journal of Environmental Economics and Management, 2022)
Organic fertilizers have been reported to increase the yield and quality of crops as well as soil properties. Production of organic based fertilizers help to convert wastes which would otherwise become a nuisance to the environment to environmentally friendly and agriculturally useful materials. The research work was done using different materials such as neem seeds, calcium carbonate, bone mill, blood mill, rice husk and potash. The production of the fertilizer was done by mixing the materials and taken to the hammer mill for milling. Finally, the milled fertilizer was taken to the granulator for granulation and later dried off and packaged. The chemical analysis of the finished product was carried out by different methods; Nitrogen (N) was analyzed by kjelahl method, Phosphorus (P) by brary & kurtz no.1 method, potassium (k) flame photometric method and organic carbon (c) by walkeley-black method. The result of the analysis is: Nitrogen (N) 0.672%, Phosphorous (P) 5.17 mg/kg, Potassium (K) 11.50 mg/kg, and Organic Carbon (C) 3.890. This project serves as the hands-on training venue for organic fertilizer production not only for university students but also for outside clients. The conversion of solid wastes into a valuable resource such as organic compost or organic fertilizer is a worthwhile strategy for saving the Earth from further degradation generated by improper waste disposal and management. Moreover, the continuous use of organic fertilizer as a source of plant nutrients for agricultural production not only reduces the cost of fertilizer but serves as the ultimate solution for restoring the lost fertility of agricultural soils as well as soil health; this leads to sustained soil productivity. It is recommended that techno guide on solid waste composting for the production of organic fertilizer should be disseminated to people to solve waste disposal problems through conversion of biodegradable wastes into organic compost; this will ensure the availability of organic fertilizer for crop production.